Survei PPLP Tenis Meja Gorontalo - Idris, Firmansyah Is; Datau, Suriyadi; Amri, Muhammad Faisal Lutfi (-, 2025)
The purpose of this research is to find out: (1) Organizational management of Gorontalo Table Tennis PPLP (2) Achievement Development of Gorontalo Table Tennis PPLP (3) Infrastructure and facilities available at Gorontalo Table Tennis PPLP (4) Training methods implemented by Gorontalo Table Tennis PPLP (5) Achievements that have been achieved by Gorontalo Table Tennis PPLP. The research results were obtained as follows: (1) The organization of Gorontalo Table Tennis PPLP is good, because the organization has been equipped with elements that support the running of the organization and there is a good division of labor. (2) Achievement coaching that is carried out is good, because the coaching is carried out through stages of coaching which includes elements of massaging, breeding and talent scouting. (3) The infrastructure and facilities owned by PPLP are quite good, because they can support the smooth running of training in advancing athlete achievement coaching but still need more attention regarding existing facilities. (4) The training program is good, there is already a daily training program which includes basic technical training and physical and mental training as well as a mini competition as a training evaluation event before participating in the upcoming championship. (5) The achievements achieved by PPLP Gorontalo Table Tennis at the National level are in the good category, this can be seen from every championship held at the National level.